COVID-19 Crisis Communication in Tourist Destinations in the Basque Country and Valencian Community - San Juan Olmo, Andrea; Sarmiento Guede, José Ramó; García de Blanes Sebastián, María; Carvajal Camperos, Marisol (Revista Venezolana de Gerencia, 2024)
It is crucial to understand how tourist destinations in Spain handled social media communication during the health crisis in order to assess its effectiveness and learn from the strategies implemented. This study describes the crisis management and communication of Spanish tourist destinations during the pandemic through their social media profiles, focusing on “Turismo Euskadi” and “Turismo de la Comunitat Valenciana”. A content analysis of the social media profiles (Twitter) of tourist destinations was used. The research revealed that tourist destinations in Spain prioritized informative and crisis communication on their social media profiles during the pandemic. The findings highlighted the importance of empathetic and effective social media communication to manage crises in tourist destinations during the pandemic in Spain.